2017
DOI: 10.1021/acs.biochem.7b00547
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cβ3 Membrane Adsorption and Activation Are Regulated by Its C-Terminal Domains and Phosphatidylinositol 4,5-Bisphosphate

Abstract: Phospholipase Cβ (PLCβ) enzymes hydrolyze phosphatidylinositol 4,5-bisphosphate to produce second messengers that regulate intracellular Ca, cell proliferation, and survival. Their activity is dependent upon interfacial activation that occurs upon localization to cell membranes. However, the molecular basis for how these enzymes productively interact with the membrane is poorly understood. Herein, atomic force microscopy demonstrates that the ∼300-residue C-terminal domain promotes adsorption to monolayers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 78 publications
2
29
0
Order By: Relevance
“…the distal C-terminal domain is a coiled-coil domain with highly conserved clusters of lysine and arginine residues arrayed along one face that function as a major membrane binding determinant. Indeed, the membrane acts as an allosteric activator of PLCs [198,199]. Thus conceptually, the model that PLCβ3 only hydrolyzes ORP4L-extracted lipid is at odds with our general understanding of how PLCβ enzymes work in general.…”
Section: Plcβ3mentioning
confidence: 99%
“…the distal C-terminal domain is a coiled-coil domain with highly conserved clusters of lysine and arginine residues arrayed along one face that function as a major membrane binding determinant. Indeed, the membrane acts as an allosteric activator of PLCs [198,199]. Thus conceptually, the model that PLCβ3 only hydrolyzes ORP4L-extracted lipid is at odds with our general understanding of how PLCβ enzymes work in general.…”
Section: Plcβ3mentioning
confidence: 99%
“…PLC␤3-⌬892 and reduced PLC␤3-⌬892 E60C/V164C were purified as described previously (54). Oxidized PLC␤3-⌬892 E60C/V164C was purified similarly, but reducing agents were omitted in each step.…”
Section: Conformational Dynamics Of Plc Enzymesmentioning
confidence: 99%
“…DSF assays were carried out as described previously (40,54), with minor modifications. Purified PLC⑀ (0.2-0.6 mg/ml) and PLC␤ variants (0.5 mg/ml) were incubated with 5ϫ SYPRO orange dye in the presence of 5 mM CaCl 2 .…”
Section: Differential Scanning Fluorimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive analyses of some of the PLC enzymes also identified specific features involved in regulation of a particular family and suggested that membrane interactions could be quite complex, with multiple roles. In this respect, members of the PLC family have been studied most extensively; in addition to structural studies (13)(14)(15)(16)(17), regulation of these enzymes has been analyzed in the presence of different model membranes in vitro (21)(22)(23)(24)(25). In its basal state, PLC is autoinhibited by the XY-linker from the catalytic TIM barrel and by elements from the C-terminal domain, representing a unique feature of PLC enzymes.…”
Section: Introductionmentioning
confidence: 99%